High temperature nanoindentation characterisation of P91 and P92 steel - Davies, Michael I. (2013)
Modern demands in power generation call for higher efficiencies from every area of the power plant. One aspect of this is a drive to increase plant operating temperatures placing higher demand on structural materials. P91 and P92 are two steels commonly used in steam pipes. In order to accurately predict the service lifetime of components, mechanical properties at operating temperatures are critical. In particular properties of material around weld fusion joints are of interest as it is in these regions where failures occur.